Familial Normokalemic Periodic Paralysis Associated With Mutation in the SCN4A p.M1592V - Fu, Chao; Wang, Zhenyu; Wang, Libo; Li, Jia; Sang, Qiuling; Chen, Jiajun; Qi, Ling; Jin, Hui; Liu, Xiaoyang (Frontiers in Neurology, 2018)
Periodic paralysis (PP) is an uncommon inherited disorder causing recurrent episodes of muscle weakness, with an incidence of 0.001%. Normokalemic periodic paralysis (NormoKPP) as the rarest subtype of PP contains both familial and sporadic. Familial NormoKPP caused by the p.M1592V mutation of the skeletal muscle sodium channel alpha subunit (SCN4A) gene is rarely reported. Only three pedigrees of NormoKPP related to mutations in the SCN4A p.M1592V have been previously reported. We herein presented a family case of NormoKPP associated with the SCN4A p.M1592V mutation, in which respiratory muscle paralysis occurred in the proband while not in his children. Moreover, we conducted a thorough literature review. To our knowledge, this is the first report of respiratory muscle paralysis as a symptom of NormoKPP associated with mutation in the SCN4A p.M1592V.